THE EFFECTIVENESS OF SELF-COMPASSION AND SELF-ESTEEM WRITING TASKS IN IMPROVING POSITIVE BODY IMAGE AND MENTAL HEALTH: A RANDOMIZED CONTROLLED TRIAL - Faria, Cristiany Seppe; de Oliveira, Natália Christinne Ferreira; Campos, Erick Carvalho; Meireles, Juliana Fernandes Filgueiras; de Carvalho, Pedro Henrique Berbert; Neves, Clara Mockdece (ARACÊ, 2025)
The present study aimed to evaluate the effectiveness of a brief online intervention to promote positive body image and other aspects related to mental health. Ninety-four Brazilian college students of both sexes were randomly assigned to one of three groups: self-compassion, self-esteem, or control written intervention. The participants responded to instruments measuring self-compassion, self-esteem, body appreciation, body functionality appreciation, symptoms of anxiety, depression, and common mental disorders before the intervention, immediately after the intervention, and two weeks after the intervention (follow-up). This is therefore a randomized clinical trial of 3 x 3 design, with a parallel, three-arm, single-blind intervention model. The results indicated an effect of time on self-compassion, body appreciation, depression symptoms, and common mental disorders. No group effects were found for any of the variables under study. A group and time interaction effect was found for only the overidentification subscale of the self-compassion measure. The results are discussed in light of brief interventions, with emphasis on the roles of sociocultural variables, the online format of the intervention, and the timing of the COVID-19 pandemic, which may have played important roles in the effectiveness of the interventions conducted.